Endoscopic Ultrasound (EUS)-Directed Transgastric Endoscopic Retrograde Cholangiopancreatography or EUS: Mid-Term Analysis of an Emerging Procedure - Amy Tyberg; Jose Nieto; Sanjay Salgado; Kristen Weaver; Prashant Kedia; Reem Z. Sharaiha; Monica Gaidhane; Michel Kahaleh (Clinical Endoscopy, 2017)
Background/Aims Performing endoscopic retrograde cholangiopancreatography (ERCP) in patients who have undergone Rouxen-Y gastric bypass (RYGB) is challenging. Standard ERCP and enteroscopy-assisted ERCP are associated with limited success rates. Laparoscopy- or laparotomy-assisted ERCP yields improved efficacy rates, but with higher complication rates and costs. We present the first multicenter experience regarding the efficacy and safety of endoscopic ultrasound (EUS)-directed transgastric ERCP (EDGE) or EUS. Methods All patients who underwent EDGE at two academic centers were included. Clinical success was defined as successful ERCP and/or EUS through the use of lumen-apposing metal stents (LAMS). Adverse events related to EDGE were separated from ERCP- or EUS-related complications and were defined as bleeding, stent migration, perforation, and infection. Results Sixteen patients were included in the study. Technical success was 100%. Clinical success was 90% (n=10); five patients were awaiting maturation of the fistula tract prior to ERCP or EUS, and one patient had an aborted ERCP due to perforation. One perforation occurred, which was managed endoscopically. Three patients experienced stent dislodgement; all stents were successfully repositioned or bridged with a second stent. Ten patients (62.5%) had their LAMS removed. The average weight change from LAMS insertion to removal was negative 2.85 kg. Conclusions EDGE is an effective, minimally invasive, single-team solution to the difficulties associated with ERCP in patients with RYGB.